Application of Dijkstra's Algorithm to Determine the Shortest Route from City Center to Medan City Tourist Attractions - Liskedame Yanti Sipayung; Chaston Ramotto Sinaga; Angelica Claudia Sagala (Journal of Computer Networks, Architecture and High Performance Computing, 2023)
Tourist attractions are very interesting things to visit in an area that we are living. It is no exception when visiting the city of Medan, the tourists will visit interesting tourist spots in the city of Medan. To optimize time so that you can visit all tourist attractions in Medan City, you need to map locations so that you can create the shortest route that can be used to take all the tourist sites you want to visit in Medan City. The shortest route of a trip will shorten the travel time. Likewise in terms of seeking experts. When requesting a route from one point (start point) to another location (destination point), usually the result that comes out is the "shortest path" from the starting point to the destination point. The shortest path is the problem of finding a path between two or more vertices in a minimum weighted graph. To simplify solving the shortest path problem, a search algorithm is needed. Dijkstra's algorithm solves the problem of finding the shortest path between two vertices in a weighted graph with the smallest total number, by finding the shortest distance between the initial vertex and other vertices, so that the path formed from the initial vertex to the destination vertex has the smallest total weight. In this study, Dijkstra's algorithm looks for the shortest path based on the smallest weight from one point to another, so that it can help provide a choice of paths. Based on the trials of Dijkstra's algorithm, it has the ability to find the shortest path, because in this algorithm each graph is selected an edge with a minimum weight that connects the selected vertices with other unselected vertices.